A Novel CLN6 Variant Associated With Juvenile Neuronal Ceroid Lipofuscinosis in Patients With Absence of Visual Loss as a Presenting Feature - Nicolaou, Paschalis; Tanteles, George A.; Votsi, Christina; Zamba-Papanicolaou, Eleni; Papacostas, Savvas S.; Christodoulou, Kyproula; Christou, Yiolanda-Panayiota (Frontiers in Genetics, 2021)
The neuronal ceroid lipofuscinoses (NCLs), also known as Batten disease, are a group of autosomal recessive lysosomal storage disorders that are characterised by neurodegeneration, progressive cognitive decline, motor impairment, ataxia, loss of vision, seizures and premature death. To date pathogenic variants in more than 13 genes have been associated with NCLs. CLN6 encodes an ER non-glycosylated transmembrane protein, which is involved in lysosomal acidification. Mutations in CLN6 cause late-infantile neuronal ceroid lipofuscinosis (LINCL), juvenile (JNCL) adult onset NCL and Kufs disease. Members from two available families with JNCL were clinically evaluated and samples were collected from consenting individuals. Molecular investigation was performed by whole exome sequencing, Sanger sequencing and family segregation analysis. Furthermore, in silico prediction analysis and structural modelling of the identified CLN6 variants were performed. We report clinical and genetic findings of three patients from two Greek-Cypriot families (families 915 and 926) with JLINCL. All patients were males and the first symptoms appeared at the age of six years. The proband of family 926 presented with loss of motor abilities, ataxia, spasticity, seizure and epilepsy. The proband of family 915 had ataxia, spasticity, dysarthria, dystonia and intellectual disability. Both probands did not show initial sighs of vision and/or hearing loss. Molecular analysis of family 926 revealed two CLN6 biallelic variants; the novel, de novo p.Tyr295Cys, and the known, p.Arg136His variants. In family 915, both patients were homozygous for the p.Arg136His CLN6 variant. Prediction analysis of the two CLN6 variants characterised them as probably damaging and disease causing. Structural modelling of the variants predicted that they probably cause protein structural differentiation. In conclusion, we describe two unrelated Cypriot families with JNCL. Both families had variants in the CLN6 gene; however, they presented with slightly different symptoms and notably none of the patients has loss of vision. In silico prediction and structural analyses indicate that both variants are most likely pathogenic. Keywords: Neuronal Ceroid Lipofuscinosis (NCL), Batten disease, CNL6, Next-Generation Sequencing (NGS), lysosomal storage disorders, in silico prediction.